THE EFFECT OF TAX ADMINISTRATIVE REFORM, TAX KNOWLEDGE AND TAX SERVICE PERFORMANCE ON TAXPAYER COMPLIANCE AT KPP PRATAMA MEDAN EAST - Oktavia, Risca Angel (Proceeding International Seminar of Islamic Studies, 2024)
This research is research conducted to test and analyze tax administration reform, tax knowledge and tax service performance on taxpayer compliance at KPP Pratama Medan Timur, with an associative research approach, and data collection techniques by distributing questionnaires, with a sample of 100 respondents and using multiple linear regression analysis technique using the SPSS application. Based on the research results, it was concluded that tax administration reform had a significant positive influence on taxpayer compliance at KPP Pratama East Medan, Tax knowledge had a significant positive influence on taxpayer compliance at KPP Pratama East Medan, Tax Service Performance had a significant positive influence on taxpayer compliance at East Medan Pratama KPP and tax administration reform, tax knowledge and tax service performance have a significant positive influence on taxpayer compliance at East Medan Pratama KPP.